2019
DOI: 10.3892/mmr.2019.10440
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in the level of WT1 as an MRD marker to predict the therapeutic outcome of patients with AML with and without allogeneic stem cell transplantation

Abstract: Monitoring minimal residue disease (Mrd) is an effective approach to evaluate the response to chemotherapy, and it is used to select the ideal therapeutic strategy and to predict the recurrence during therapy for hematological disorders. The Wilm's tumor 1 (WT1) gene, which is highly expressed in >80% of patients with acute myeloid leukemia (aMl) and its increased expression level may cause poor clinical outcomes, is a potential Mrd marker of hematological neoplasms. in the present study, the expression levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In addition, WT1 mRNA value positivity (≥ 50 copies/µg RNA) in PB after intensive chemotherapy or stem cell transplantation is an independent poor prognostic factor for relapse [ 24 28 ]. Therefore, WT1 mRNA value after chemotherapy can indicate disease activities such as remission and relapse [ 29 ]. This study also found that WT1 mRNA 1-log reduction by the end of cycle 2 and WT1 mRNA value negativity during the treatment cycle were associated with significantly prolonged OS and EFS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, WT1 mRNA value positivity (≥ 50 copies/µg RNA) in PB after intensive chemotherapy or stem cell transplantation is an independent poor prognostic factor for relapse [ 24 28 ]. Therefore, WT1 mRNA value after chemotherapy can indicate disease activities such as remission and relapse [ 29 ]. This study also found that WT1 mRNA 1-log reduction by the end of cycle 2 and WT1 mRNA value negativity during the treatment cycle were associated with significantly prolonged OS and EFS.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of patients with CMML do not receive chemotherapy before transplantation; hence, MRD monitoring in CMML and AML also differs. Previous studies have reported that WT1 is overexpressed in >80% of patients with AML and could be used as a marker of recurrence after achieving complete remission 31,32 . However, WT1 has not been used as an established marker for MRD monitoring in patients with CMML.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that WT1 is overexpressed in >80% of patients with AML and could be used as a marker of recurrence after achieving complete remission. 31,32 However, WT1 has not been used as an established marker for MRD monitoring in patients with CMML. FCM could distinguish abnormal immunophenotypic patterns expressed on leukemic cells.…”
Section: F I G U R Ementioning
confidence: 99%
“…However, in this case, abnormal up-regulation of WT1 was not observed at different stages, but the WT1 variant persisted. Similar to the WT1 mutation being related to poor prognosis [ 14 ], WT1 overexpression was also indicated to be associated with shorter OS [ 15 ]. However, the question remains, which alteration could be a potential indicator of prognostic stratification for the patient; expression level or mutation status?…”
Section: Discussionmentioning
confidence: 99%